DETERMINAN KEBUTUHAN SAK ETAP BAGI UKM (Studi Empiris Pada UKM Makanan di Kota Semarang) - Faizatuz Zahro; Sri Dewi Wahyundaru (Conference In Business, Accounting, And Management (CBAM), 2015)
SAK ETAP level needs for SMEs is very low and also still considered burdensome SMEs. The study entitled